AN ANALYSIS OF PRICE NEGOTIATION STRATEGIES WITH CUSTOMERS AT A FASHION, ACCESSORIES AND HIJAB STORE (A Study Of Tasya Collection) - Pelly wartini Nst; Teuku Fahmi; Asrindah Nst (Universitas Dharmawangsa Medan, 2026)
This research analysed the price negotiation strategies employed at Tasya Collection, a fashion businessspecializing in the sale of hijabs and women’s accessories. The negotiation process between sellers and buyersis the primary focus, as many customers have complained about prices being higher than those found in onlineshops, as well as a lack of flexibility in bargaining. This study employs a descriptive qualitative method, withdata collected through direct observation and the author’s four years of work experience at the shop. Thefindings indicate that current price negotiation strategies remain limited, with a maximum discount of only Rp5,000, regardless of customer loyalty or purchase volume. This strategy is considered ineffective in maintainingcustomer satisfaction and enhancing the shop’s competitiveness. Therefore, it is recommended that the shopowner adopt a more flexible and responsive negotiation approach to better meet consumer needs.Keywords: price negotiation, sales strategy, customer satisfaction, fashion shop, Tasya Collection